Study of buzz phenomenon in suddenly expanded flow structure using experiments and visualization. (3rd October 2021) - Quadros, Jaimon D.; Khan, S. A.; Prashanth, T.
Abstract: Experimental investigations have been carried out on a suddenly expanded duct in a view to determine buzz phenomenon for different Mach numbers (M), nozzle pressure ratios (NPR), and mass flow rates (MFR). The experimental facility was designed with sensitive and high-frequency pressure controls. The experiments were conducted for Mach numbers ranging from 2.0 to 3.0, with multiple NPRs of 3, 5, 7, and 9. In combination with the high-speed camera, shadowgraph mapping techniques were employed to provide optical depiction of the shock system in front of the inlet and to study the buzz features. Displacement of the shock and buzz frequency were calculated by shadowgraphs. The information gathered from the shadowgraphs was assessed against the pressure measurements and the values were in good agreement with each other. The results observed that for nominal values of MFR, the buzz frequency decreased with increasing Mach number. Furthermore, for an increasing NPR, the shock displacement further increases. The results also showed that there were significant pressure fluctuations in the expanded duct for lower Mach numbers.